2019
DOI: 10.1155/2019/1572196
|View full text |Cite
|
Sign up to set email alerts
|

Succinate-Based Dietary Supplement for Menopausal Symptoms: A Pooled Analysis of Two Identical Randomized, Double-Blind, Placebo-Controlled Clinical Trials

Abstract: Background To evaluate the efficacy of a succinate-based dietary supplement (SBDS; Amberen) in symptomatic menopausal women using a larger sample size derived by pooling data from two identical trials. Methods Raw data were pooled from two identical randomized, multicenter, double-blinded, placebo-controlled, 90-day clinical trials. Women aged 42–60 years with mild to moderate vasomotor and psychosomatic menopausal symptoms were included (114 in the treatment group and 113 in the placebo group). Symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…An ammonium succinate-based supplement (Amberen) was studied for the management of menopause symptoms in a manufacturer-sponsored clinical trial, with an initial study published in 2016, 143 and later a pooled analysis including this study and a second additional study was published in 2019. 144 The studies were identical multicenter, double-blind, 90-day RCTs including women aged 42 to 60 years with mild to moderate menopause symptoms (n = 227). Both studies showed improvement in menopause symptoms such as sleep, fatigue, loss of interest in sex, joint and muscle pain, VMS, and a decrease in anxiety compared with the placebo group.…”
Section: Ammonium Succinatementioning
confidence: 99%
“…An ammonium succinate-based supplement (Amberen) was studied for the management of menopause symptoms in a manufacturer-sponsored clinical trial, with an initial study published in 2016, 143 and later a pooled analysis including this study and a second additional study was published in 2019. 144 The studies were identical multicenter, double-blind, 90-day RCTs including women aged 42 to 60 years with mild to moderate menopause symptoms (n = 227). Both studies showed improvement in menopause symptoms such as sleep, fatigue, loss of interest in sex, joint and muscle pain, VMS, and a decrease in anxiety compared with the placebo group.…”
Section: Ammonium Succinatementioning
confidence: 99%
“…Further, reduction of liver α-ketoglutaric acid and lactate, two critical intermediates for glycolysis, also suggested paternal ZnD altered the balance of glycolysis and affected TCA cycle. It is reported that succinate could provide an energy supply and catecholamine-like influence on the hypothalamus and increase the organ's sensitivity to input signals from peripheral endocrine glands, therefore elevating succinate in the liver, which may in turn affect the TCA cycle ( Radzinsky et al., 2019 ). Nevertheless, a lesser effect of paternal ZnD on glycolysis was found.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of two RCTs by Radzinsky et al (2019) found a significant benefit following 3 months of a multi‐nutrient intervention. However, the RCTs were conducted by the same research group and so corroborative evidence from other groups would be useful (Ataei‐Almanghadim et al., 2020; Radzinsky et al, 2019).…”
Section: Symptoms Of the Menopausementioning
confidence: 99%